2012
DOI: 10.1111/j.1551-2916.2012.05088.x
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Bismuth‐Based Oxides in Organic‐Inorganic Hybrid Photovoltaic Devices

Abstract: Bismuth‐based ferroelectric oxide films including BiFeO3, Bi2WO6 and BiVO4 with different band structure are prepared by pulsed laser deposition method and used as n‐type semiconductors in photovoltaic devices. The oxide films are combined with p‐type organic semiconductor poly(3‐hexylthiophene) to form bilayer heterojunctions and their photovoltaic effects are systematically studied. Compared with some other oxide semiconductors, such as ZnO or TiO2, the bismuth‐based oxides exhibit wider absorption spectra a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
(104 reference statements)
2
21
0
Order By: Relevance
“…5 shows the J-V curves that illustrate the photovoltaic Upon irradiation the open circuit voltage was nearly unchanged, but the maximum current density increased to 0.05 mA cm À 2 . Although the absolute power conversion efficiency is low ( $ 0.01%), it is comparable with previously published values for BiFeO 3 layers grown by pulsed laser deposition [32]. One source of the low power conversion efficiency is presence of oxygen vacancies in the BiFeO 3 layer, which serve as n-type donors and act as recombination centers.…”
Section: Resultssupporting
confidence: 84%
“…5 shows the J-V curves that illustrate the photovoltaic Upon irradiation the open circuit voltage was nearly unchanged, but the maximum current density increased to 0.05 mA cm À 2 . Although the absolute power conversion efficiency is low ( $ 0.01%), it is comparable with previously published values for BiFeO 3 layers grown by pulsed laser deposition [32]. One source of the low power conversion efficiency is presence of oxygen vacancies in the BiFeO 3 layer, which serve as n-type donors and act as recombination centers.…”
Section: Resultssupporting
confidence: 84%
“…Unfortunately, there have been few researches on BiVO 4 based solar cells. Liu et al [17] investigated bilayer P3HT-BiVO 4 hybrid solar cell with a power conversion efficiency (PCE) of 0.08%. Zhang et al [18] reported a Mo-doped BiVO 4 (~50 nm) liquidjunction photovoltaic solar cell in I − /I 3 − electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The 36% enhancement in power‐conversion efficiency η is obtained because the lowest unoccupied molecular orbital (LUMO) of P3HT is above the Bi 2 O 3 conduction band. The E LUMO (P3HT) − E CB (Bi 2 O 3 ) difference shows an enthalpy driving force for electron injection from P3HT to Bi 2 O 3 . Similarly, because the highest occupied molecular orbital (HOMO) of P3HT is below Au, it creates a driving force for hole injection into the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Bismuth oxide (Bi 2 O 3 ) as an inorganic oxide is an interesting semiconductor material. Because of its strong absorption of visible light and intrinsic polarizability, Bi 2 O 3 has exhibited PV properties . Bi 2 O 3 films can absorb visible light in the short‐wavelength region (below 600 nm) and match the absorption spectrum of conjugated polymers of poly(3‐hexylthiophene) (P3HT) .…”
Section: Introductionmentioning
confidence: 99%